PLATELET DISINTEGRATION DURING CLOTTING - Rodman, N. F. (The Rockefeller University Press, 1963)
Sequential alterations in the ultrastructure of blood platelets observed during the clotting of human platelet-rich plasma are described, with emphasis on disintegration of the platelet. As the clotting reaction proceeds, aliquots of citrated and recalcified citrated plasma are fixed by adding buffered OsO(4). After recalcification a lag period of about 10 minutes is followed by an interval of rapidly occurring changes which include reorientation of cytoplasmic contents, progressive central degeneration, and disruption of the platelet limiting membrane. Shortly thereafter vesicular platelet remains are seen at the peripheries of loosely arranged and widely spaced masses of granular material. As clot retraction proceeds, these masses gradually come closer together, become more and more compact, and finally disappear. At the same time the vesicles undergo progressive disintegration until at the end of the experiment, 2 hours after recalcification, only a few are found randomly distributed in a dense clot. The significance of progressive disintegration and the origin of the vesicles observed in the later stages of the experiment are discussed in relation to clot formation and clot retraction.